Characterization of indoor power lines as data communication channels experimental details and results - Khan, Sheroz; Salami, Abdulazeez F.; Lawal, Wahab Adetunji; Alam, A. H. M. Zahirul; Abdel Hameed, Shihab; Salami, Momoh Jimoh Emiyoka (International Research Publication House, 2009)
In this paper, a multi-branch power line is modeled using ABCD matrix to show its worth as a communication channel. The model is simulated using MATLAB in an effort to investigate the effects of multiple loading, multipath, and those as a result of load mismatching. The channel transfer function is obtained and investigated using different cable lengths, and different number of bridge taps under given loading conditions.